Metabolic energy expenditure of ambulation in lower extremity amputees: what have we learned and what are the next steps?. Issue 2 (16th January 2017) - Czerniecki, Joseph M.; Morgenroth, David C.
Abstract: Purpose : Amputation results in reduced mobility and contributes to reduced quality of life. The increased metabolic cost of ambulation has been suggested as an important contributor to reduced mobility in this population. Current research on the metabolic energy expenditure of ambulation will be critically reviewed from the perspectives of ecological validity of the research methods and the relative contribution to functional improvement in amputees. Recommendations will be made regarding possible future directions for research and their potential clinical utility. Methods : Narrative review. Results : The methods used to quantify metabolic energy expenditure of amputee ambulation do not emulate typical mobility conditions that amputees experience. Amputee mobility is characterized by short bouts of activity with starting, stopping and changes of direction. This is opposed to the typical metabolic testing protocol that requires at least 5 min of steady state linear walking on a treadmill. These studies, therefore, have limitations in ecological validity and therefore limitations in the extent to which they accurately reflect the effect of amputation level, amputation etiology and prosthetic components on energy consumption during walking. Further, the broader perspective on outcomes after dysvascular amputation and sports participation limitations, raises questions about the relative importance of improving metabolic costs and its potential effect on improving mobility in amputees. Conclusion : The greatest potential clinical impact of future research requires methods with improved ecological validity, and the ability to translate metabolic energy expenditure outcomes into functional terms that are meaningful to both clinicians and patients. Implications for Rehabilitation: The search for objective measurements to define the effects of amputation on outcome and the consequences of prosthetic components on mobility has focused in part on the use of study designs incorporating metabolic measurement. However, there are important limitations to the ecological validity of these measures and their relative importance as an outcome measure in dysvascular amputees as well as in sports/leisure participation. Novel research approaches are required to quantify the functional impact of increased metabolic energy expenditure and to better understand the psychophysical limitations that result.